2012
DOI: 10.4081/rt.2012.e32
|View full text |Cite
|
Sign up to set email alerts
|

Neurological Manifestation of Colonic Adenocarcinoma

Abstract: Paraneoplastic neurologic disorders are extremely rare in cancer patients and are most commonly associated with certain tumors, such as ovarian cancer, small cell lung cancer, and breast cancer. We report here a paraneoplastic neurological syndrome in a 53-year-old man with colonic adenocarcinoma with a solitary liver metastasis. His paraneoplastic syndrome was successfully treated by methylprednisolone and primary oncologic therapies including neoadjuvant chemotherapy and definitive surgery. This is also the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…In all the reported cases, [ 4 6 ] the neurological symptoms preceded the diagnosis of tumor, and in one of them they coincided with tumor progression; [ 7 ] differently, our patient developed the PLE 4 years after the radical resection of the primary colon cancer and 2 months after the diagnosis of metastases from colon neoplasm, while receiving a very active first-line chemotherapy by which a partial reduction of the tumor burden was obtained.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…In all the reported cases, [ 4 6 ] the neurological symptoms preceded the diagnosis of tumor, and in one of them they coincided with tumor progression; [ 7 ] differently, our patient developed the PLE 4 years after the radical resection of the primary colon cancer and 2 months after the diagnosis of metastases from colon neoplasm, while receiving a very active first-line chemotherapy by which a partial reduction of the tumor burden was obtained.…”
Section: Discussionmentioning
confidence: 75%
“…Sio et al [ 4 ] describe the story of a 53-year-old man who simultaneously developed a sensory neuropathy and a limbic encephalitis. The diagnosis of metastatic colon cancer was done during the diagnostic work-up for the neurologic symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…However, no testing for neuro-oncologic antibodies was performed. Paraneoplastic neurological syndromes due to colon cancer are extremely rare, with sensory neuropathy and vasculitis having been described [ 11 ]. Of note, it has been observed that tumors causing paraneoplastic neurologic disorders are often “heavily infiltrated with inflammatory cells” and have a better prognosis than histologically identical tumors with no paraneoplastic neurologic manifestations [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“… 2 We aim to collect, analyze, and ultimately publish quality clinical data on either a rare type of cancers in which radiotherapy and/or chemoradiation play an important role, or rare presentations of common cancers which are of interest to the globally practicing radiation oncologists, including management of unusual paraneoplastic syndromes. 3 , 4 The most common tool for clinical investigation is typically retrospective methods, however, prospectively followed protocols and registries (J. Thariat) and case control studies (other investigators) have been previously proposed. The announcement of new studies must first be coordinated with the secretariat office (B. Pointet) so that RCN research activities can be tracked.…”
Section: A Brief History Of the Rare Cancer Networkmentioning
confidence: 99%